Assessment of Liver Perfusion by IntraVoxel Incoherent Motion (IVIM) Magnetic Resonance–Diffusion-Weighted Imaging. Issue 3 (May 2015) - Regini, Francesco; Colagrande, Stefano; Mazzoni, Lorenzo Nicola; Busoni, Simone; Matteuzzi, Benedetta; Santini, Paolo; Wyttenbach, Rolf
<x xml:space="preserve">Abstract</x> Objectives To prospectively verify, in vivo, Le Bihan's model of signal decay in magnetic resonance/diffusion-weighted imaging (intravoxel incoherent motion) in healthy liver parenchyma. Methods Informed consent and institutional board approval were obtained. To measure both underfasting and postprandial conditions, apparent, slow, and fast diffusion (D*) coefficients and perfusion fraction of liver parenchyma, 40 healthy volunteers (19 women and 21 men) underwent a 3.0-T magnetic resonance imaging examination, including portal venous flow measurements by a 2-dimensional phase-contrast sequence, and multi-b diffusion-weighted imaging acquired before and 30 minutes after a 600-Kcal meal. Parameters were measured by fitting procedure with regions of interest drawn on the right liver lobe. Paired-sample t test was performed to search for any statistically significant difference between preprandial and postprandial values of each parameter and of portal flow. Pearson correlation coefficients were calculated to evaluate the relationship between portal flow increase and diffusion-weighted imaging parameter changes in postprandial conditions. Interobserver agreement for measurement of the intravoxel incoherent motion parameters was determined, both for preprandial and postprandial values. Results Mean increase in postprandial portal flow was 98% (P < 0.0009). The t test did not show any statistically significant difference between the preprandial and postprandial values for apparent, slow diffusion coefficients and perfusion fraction (P ≥ 0.05), whereas a statistically significant postprandial increase (P < 0.01) of D* was detected. Correlation with portal venous flow increase at Pearson test was statistically significant for D* (P = 0.04) and nonsignificant for the other parameters. All the parameters showed wide variability, with a higher percent coefficient of variation for D*. Interobserver agreement was always greater than 0.70. Conclusions This study verifies Le Bihan's theory, confirming that in the liver, D* is influenced by perfusional changes related to portal venous flow.